Connection Mechanism Capable of Genderless Coupling for Modular Manipulator System - Hong, Seonghun; Lee, Woosub; Kim, Kanggyun; Lee, Hyeongcheol; Kang, Sungchul (2017 14TH INTERNATIONAL CONFERENCE ON UBIQUITOUS ROBOTS AND AMBIENT INTELLIGENCE (URAI), 2017)
Gender characteristics of connecting side between modules affects the number of configurations after assembly of modular manipulator systems. A modular connection mechanism capable of genderless coupling of mechanical and electrical connection between modules is introduced. The connection can be established between two modules via four types of relative positions of 90 intervals.